Incentives for improving municipal solid waste source separation behaviour: the case of Tamale Metropolis, Ghana. - Asare, Wilhemina; Oduro-Kwarteng, Sampson; Donkor, Emmanuel (Springer Link, 2021)
Source separation is a key step to increase waste diversion and can promote recycling by providing the needed raw materials. This study analyzed solid waste separation activities and incentive options through a survey conducted in households in four different solid waste management service zones. The study was conducted to evaluate preferences for solid waste separation activities and incentives in the service zones to identify options that can promote positive solid waste separation behaviours among households to aid the diversion of reusable and recyclable materials from the landfill. Multivariate probit analysis was conducted on proposed incentive choices by households which highlighted the key incentive options that can be used to improve household waste separation behaviour for effective solid waste separation at the households. The result of the study indicates that the majority of the respondents prefer the provision of free bins as an incentive to voluntarily participate in waste separation programmes. Cash fines were discovered as a sanction to coerce householders to comply with mandatory solid waste separation in the service zones. The study established that some of the proposed incentives may have complementary roles if used as motivation in a recycling scheme while others may serve as substitutes in supporting waste separation or recycling behaviour in the service zones. The results again indicate that incentives are significant predictors of solid waste separation behaviour in the service zones, however, its effects on waste separation behaviour depends on the incentive used and the service zone.
SN Social Sciences volume 1, Article number: 132 (2021)
Keywords: Source separation; Municipal solid waste; Options; incentives; Recycling; behaviour; STEM; University of Port Harcourt; Mizpah Rockson